Tibiofemoral Cartilage Contact Differences Between Level Walking and Downhill Running. Issue 4 (4th April 2019) - Akpinar, Berkcan; Thorhauer, Eric; Tashman, Scott; Irrgang, James J.; Fu, Freddie H.; Anderst, William J.
Background: Some studies have suggested that altered tibiofemoral cartilage contact behavior (arthrokinematics) may contribute to long-term cartilage degeneration, potentially leading to tibiofemoral osteoarthritis. However, few studies have assessed normal tibiofemoral arthrokinematics during dynamic activities. Purpose: To characterize tibiofemoral arthrokinematics during the impact phase of level walking and downhill running. Study Design: Descriptive laboratory study. Methods: Arthrokinematic data were collected on uninjured knees of 44 participants (mean age, 20.7 ± 6.6 years). Using a dynamic stereoradiographic imaging system with superimposed 3-dimensional bone models from computed tomography and magnetic resonance imaging of participant-specific tibiofemoral joints, arthrokinematics were assessed during the first 15% of the gait cycle during level walking and the first 10% of the gait cycle during downhill running. Results: During level walking and downhill running, the medial compartment had a greater cartilage contact area versus the lateral compartment. Both compartments had a significantly less cartilage contact area during running versus walking (medial compartment gait cycle affected: 8%-10%; lateral compartment gait cycle affected: 5%-10%). Further, medial and lateral compartment tibiofemoral contact paths were significantly more posterior and longer during downhill running. Conclusion: There was a decreased tibiofemoral cartilage contact area during downhill running compared with level walking, suggesting that underlying bone morphology may play a key role in determining the size of cartilage contact regions. Clinical Relevance: This study provides the first data characterizing tibiofemoral cartilage contact patterns during level walking and downhill running. These results provide evidence in support of performing biomechanical assessments during both level walking and downhill running to obtain a comprehensive picture of tibiofemoral cartilage behavior after clinical interventions.